2014
DOI: 10.1111/josh.12149
|View full text |Cite
|
Sign up to set email alerts
|

The Researchers Have Left the Building: What Contributes to Sustaining School‐Based Interventions Following the Conclusion of Formal Research Support?

Abstract: BACKGROUND This study examined the sustainability of New Moves, a school-based program aimed at decreasing weight-related problems in adolescent girls. The National Cancer Institute recognizes New Moves as a research-tested intervention program that produced positive behavioral and psychosocial outcomes. METHODS Ten schools participated in the sustainability study. Teachers completed a survey and interview, and research staff observed one physical education (PE) class within 2 years of the study’s completion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
79
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 21 publications
4
79
0
4
Order By: Relevance
“…This is consistent with previous findings around workforce stability, administrative support, and fit with the school’s structure and priorities (e.g., Friend et al, 2014; Palinkas et al, 2013; Tibbits et al, 2010). For these clinicians, sustaining the intervention did not appear to present major challenges despite the fact that there was no longer a district-wide CBITS implementation support structure (e.g., ongoing clinical consultation, district-level support systems).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous findings around workforce stability, administrative support, and fit with the school’s structure and priorities (e.g., Friend et al, 2014; Palinkas et al, 2013; Tibbits et al, 2010). For these clinicians, sustaining the intervention did not appear to present major challenges despite the fact that there was no longer a district-wide CBITS implementation support structure (e.g., ongoing clinical consultation, district-level support systems).…”
Section: Discussionsupporting
confidence: 92%
“…De-adoption, on the other hand, can occur at any stage of the implementation process, and often refers to failure to sustain an EBP (Massatti, Sweeney, Panzano, & Roth, 2008; Panzano & Roth, 2006; Stirman et al, 2012). Currently, there is a need to understand factors and processes that may lead to EBP de-adoption under real-world conditions in which researchers and university partners are no longer providing training, consultation, personnel, or financial support (Friend, Flattum, Simpson, Nederhoff, & Neumark-Sztainer, 2014; Greenhalgh, Robert, MacFarland, Bate, & Kyriakidou, 2004). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It also recognizes the existence of a relationship between the degree of institutionalization of a program and its compatibility with the government's vision 2,9,13,35 . In this study, the intervention was strengthened by its definition as a municipal government project, supported by the population and local managers.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified factors influencing positively the sustainability of interventions -political support, funding stability, partnerships, organizational capacity, program evaluation, program adaptation, strategic planning, organizational learning, capacity building 5,6,7,8,9,10,11,12,13,14 ; and negatively -staff turnover, changing medical practice, the low level of initial implementation of the project and lack of training for participants in the intervention 15,16,17 . However, few studies have elucidated how these factors interact in this process.…”
mentioning
confidence: 99%